(untitled) (Journal of Science and Technology, 2025)
Background: Most hospitals in Low-and-Middle-Income Countries (LMICs) do not provide thrombolysis as part of routine acute stroke care. Deficiencies in healthcare providers’ knowledge levels may be an additional but neglected contributor to the low utilization of stroke thrombolysis in LMICs. Objectives: To assess the level of awareness of stroke thrombolysis among various categories of clinical staff involved in acute stroke care at Komfo Anokye Teaching Hospital (KATH), a tertiary facility in Ghana Methods: Cross-sectional surveys were conducted among health workers directly involved in acute stroke care including, internal medicine physicians, emergency physicians, residents, medical officers, house officers, and emergency and stroke nurses. Their level of knowledge regarding stroke thrombolysis was assessed. Results: About 97% of all participants (113 out of 117) were aware that thrombolysis was recommended for acute ischemic stroke treatment. However, up to 63.0% of junior staff (63.0%) were not conversant with the source of this recommendation, in contrast to 29.4% of senior staff (p=0.010). 64% of junior staff members rated their knowledge of stroke thrombolysis as either fair or poor, compared to 11.8% of senior staff members (p= 0.005). Of the junior category staff, only 42% correctly identified the recommended thrombolytic agents compared to 82.4% of senior staff (p= 0.036). Conclusion: The level of stroke thrombolysis knowledge was low among junior staff at KATH. To ensure sustainable implementation of mainstream stroke thrombolysis, targeted educational interventions should be instituted to bolster the capacity and support for stroke thrombolysis among all stroke care providers.